The Habsburgs, Venetians, Ottomans and Military Borderlands - Roksandić, Drago (2007)
Imperial military border systems of the Habsburg Monarchy, Venetian Republic and Ottoman Empire in early modern Europe have been presented and compared, paying a particular attention the the Triplex Confinium area, in which they used to confront each other for the period 16th-18th centuries.